2012
DOI: 10.5194/hessd-9-6857-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-range hydrometeorological ensemble predictions of drought parameters

Abstract: Low streamflow as consequence of a drought event affects numerous aspects of life. Economic sectors that may be impacted by drought are, e.g. power production, agriculture, tourism and water quality management. Numerical models have increasingly been used to forecast low-flow and have become the focus of recent research. Here, we consider daily ensemble runoff forecasts for the river Thur, which has its source in the Swiss Alps. We focus on the low-flow indices duration, severity and magnitude, with a forecast… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…high and low flow. Evaluating high flow is important for flood forecasting systems, and low flow, which tends to have a longer predictability is useful in hydrological drought forecasting systems, and is less often investigated than high flows (Fundel et al, 2012;Pushpalatha et al, 2012). Both of these functions are performed by EFAS and so are investigated here.…”
Section: High and Low Flowsmentioning
confidence: 98%
“…high and low flow. Evaluating high flow is important for flood forecasting systems, and low flow, which tends to have a longer predictability is useful in hydrological drought forecasting systems, and is less often investigated than high flows (Fundel et al, 2012;Pushpalatha et al, 2012). Both of these functions are performed by EFAS and so are investigated here.…”
Section: High and Low Flowsmentioning
confidence: 98%
“…A number of case studies using experimental and (pre) operational systems, however, have demonstrated their potential benefits (see, e.g., Zappa et al 2010 for references). Recent verification studies of hydrologie ensemble forecasts or hindcasts (i.e., forecasts that are retroactively generated using a fixed forecasting system) over long time periods include Bartholmes et al (2009), Jaun and Ahrens (2009), Renner et al (2009), Hopson and Webster (2010), Demargne et al (2010), Thirel et al (2010), Van den Bergh and Roulin (2010), Addor et al (2011), and Zappa et al (2012) for short-to medium-range hydrologie forecasts and Kang et al (2010), Wood et al (2011), Fundel et al (2012, Singla et al (2012), and Yuan et al (2013) for monthly to seasonal hydrologie ensembles. Objective veriflcation analysis of ensemble forecasts or hindcasts over multiple years should improve not only the science of hydrologie ensemble forecasting but also the utility…”
mentioning
confidence: 99%
“…Fundel et al . () forecasted an 18‐year (1991–2008) hydrological drought in Thur River, Switzerland, simulated from the Variable Resolution Ensemble Prediction System, a semi‐distributed hydrological model employing a lead time of 1 month. But none of them have considered ensemble prediction of droughts at different lead times, incorporating climatic information.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have addressed this issue in the context of drought prediction: Hwang and Carbone (2009) developed autoregressive drought prediction models and quantified associated forecast uncertainty using residual sampling based on modified K-NN (where K denotes the number of neighbours and NN refers to the nearest neighbour) algorithm. Fundel et al (2012) forecasted an 18-year (1991-2008) hydrological drought in Thur River, Switzerland, simulated from the Variable Resolution Ensemble Prediction System, a semi-distributed hydrological model employing a lead time of 1 month. But none of them have considered ensemble prediction of droughts at different lead times, incorporating climatic information.…”
Section: Introductionmentioning
confidence: 99%